Is there the Pareto principle in public library circulation? A case study of one public library in Taiwan - Yang, Yi-Ting; Shieh, Jiann-Cherng (Malaysian Journal of Library and Information Science, 2019)
The Pareto Principle, also known as the 80/20 rule is currently an important and popular management rule applied to marketing and customer relationship management (CRM). The rule indicates that the vital few causes inputs or efforts bringing the most results, outputs, or rewards. Analyzing circulation data to understand the usage status of library collections can help libraries comprehend their patrons’ behaviour. However, little research has been done to analyse circulation data of public libraries to reveal patrons’ usage behaviours. This paper aimed to analyse the circulation data generated by a municipality public library in Taiwan to gauge if the Pareto Principle manifested in this context. Subsequently, using bibliomining analysis, this research further identified vital patrons and their characteristics, as well as book-borrowed distributions to help analyse patrons’ book borrowing behaviour to improve the efficiency of library management and library marketing as well as CRM. The circulation data of the public library follows the Pareto Principle, approximating to the 80/20 rule. Findings showed that when the accumulative percentage of patron is 24.7 percent, the accumulative percentage of borrowed books is 75.3 percent. The vital few patrons borrow the majority of the collections. This paper is the first study to reveal that the Pareto Principle could be found in circulation data of a public library in Taiwan. It could help libraries identify vital patrons and major collections, and improve the efficiency of their management and marketing activities in future. For other types of libraries, it would be interesting for us to explore the existence of the Pareto Principle further.